EFEKTIFITAS TERAPI YOGA TERHADAP DISMENOREA PADA SISWI KELAS X SMA NEGERI 1 KLARI KABUPATEN KARAWANG PROVINSI JAWA BARAT TAHUN 2018 - Andi Julia Rifiana; Nita Istiana Sugiatno (Jurnal Ilmu dan Budaya, 2019)
Background:Prevalensi dysmenorrhea in previous research shows significant improvement. According to WHO, in average between 16,8-81%, shows the incidence of dysmenorrhea to young women. In Indonesia, dysmenorrhea shows 64.25%. In West Java, there’s no validity for percentage of dysmenorrhea. However, 30–70% women in period have a problem such as a painful in stomach. In fact, the students X in SMA Negeri 1 Klari having dysmenorrhea about 36%. Aims: The research is conducted to figure out the effectiveness of yoga dysmenorrhea therapy to the students X in SMAN 1 Klari district of Karawang, West Java in 2018. Methodology: The research used total sampling approach. Sample are collected by 44 respondents and divided into 22 which are implemented by yoga therapy and 22 respondents which are not implemented by its therapy. The research used analysis of univariat and bivariat to figure out whether there is a difference in case of painful intensity between variable that are being researched. Result and Discussion: The result of the research shows that patient with pre yoga dysmenorrhea therapy decrease in sense of painful around 6,00 and post yoga dysmenorrhea therapy decrase around 1,27 while that patient with pre not intervensi decrase in sense of painful around 6,14 and pra around 5,45 . Conclucion and suggestion: In other hand, there’s no significance result in sense of painful to patient with post yoga dysmenorrhea therapy (p-value= 0,000). The stakeholder may implement this therapy in order to decrease sense of painful to the students for woman in